Information System Design and Application of the Critical Path Method (CPM) Determining the Optimal Time for Implementing Activities - Graceae, Marsaa Noverdi; Rianti, Eva; Kurnia, Hezy (Universitas Putra Indonesia YPTK Padang, 2024)
Information is the result of processing data from one or various sources, which is then processed so that it provides value, meaning and benefits. In the modern era, the use of technology plays a very important role as a means of information and promotion, especially in the field of websites in conveying information. The activity implementation plan carried out by the institution to determine the time period for completing activities still uses estimates as a guide. These estimates result in uncertain completion times. This is of course a problem in the implementation of activities, because late completion times result in time differences with the initial planned targets. Based on these conditions, the delivery of information is felt to be less than optimal because it does not yet have a website page, so the author feels that the West Sumatra Center for Public Policy Studies (PSKP) requires an information system that is able to support activities and provide information about the institution to be more effective and efficient. Then a schedule of the activity implementation process is needed from start to finish. One method that can be used for scheduling is the critical path method (CPM). This method is part of the work network method which is oriented towards determining schedules and estimating them which are deterministic (certain). With this CPM method, all activity processes are in accordance with the initial target